IFRS and XBRL : how to improve business reporting through technology and object tracking - Ramin, Kurt P. (Wiley corporate F & A series., 2013)
International Financial Reporting Standards IFRSs are increasingly adopted worldwide, and it is critical to understand their place within the global business environment. Kurt Ramin and Cornelis Reiman, world authorities on IFRS, provide a guide to key components of IFRSs, and outline how each standard is important in a business context; they show what elements of IFRSs are crucial to local, national and international business decision making. The book covers such key issues as emerging technology in reporting under IFRS including the use of XBRL. It demonstrates the importance of dis.